Science and Truth - David Papineau (Ideas y Valores)
Philosophy of science and mainstream epistemology have much to leam from each other. Most twentienth\century philosophers of science set absurdly high standards for knowledge, and so succumb to naive sceptical arguments. They would do well to learn from mainstream epistemology that reliability is a more sensible standard for knowledge than certainty. At the same time, mainstream epistemologists would do well to learn from philosophers of science that intuitions about the everyday concept of knowledge are unimportant, by comparison with the serious issue of how to get at the truth, My own view on this latter issue is that we should look to science itself for the answers, since science itself tells us about different techniques for uncovering the truth in different subject áreas. There is nothing viciously circular in this position, though it does imply that there is no external perspective from which science as a whole can be vindicated.